Pengaruh Gaya Pengasuhan Orang Tua terhadap Efikasi Diri Keputusan Karir Siswa SMK melalui Trait Kecerdasan Emosi sebagai Variabel Mediator - Azkya Milfa Laensadi; Rose Mini Agoes Salim (Provitae: Jurnal Psikologi Pendidikan, 2020)
Adolescents undergo an important process that is deciding which career path will impact their future later. For vocational high school students, career decision making is not an easy task because there are many career choices, which is go to college, enter the workforce, or being entrepreneur. They have to be confident with themselves that they are able to make the right career decisions. This study aimed to examine the role of perceived parenting styles on career decision self-efficacy through mediation of trait emotional intelligence in vocational high school students. The respondents of the study were 702 students in 12th grade. The adapted Career Decision Self Efficacy – Short Form, Parental Authority Questionnaire, and Trait Emotional Questionnaire were used in this study. The data were analysed using Hayes’ PROCESS simple mediation model. Mediation analyses showed that trait emotional intelligence partially and positively mediated the effect of paternal and maternal authoritative parenting styles on career decision self-efficacy; trait emotional intelligence partially and negatively mediated the effect of paternal and maternal authoritarian parenting styles on career decision self-efficacy. The implication for further research is given on the end of study.